State-Contingent Debt Instruments for Sovereigns : Annexes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
These annexes accompany the IMF Policy Paper State Contingent Debt Instruments for Sovereigns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet